4(11x-3)=-1

Simple and best practice solution for 4(11x-3)=-1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(11x-3)=-1 equation:


Simplifying
4(11x + -3) = -1

Reorder the terms:
4(-3 + 11x) = -1
(-3 * 4 + 11x * 4) = -1
(-12 + 44x) = -1

Solving
-12 + 44x = -1

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '12' to each side of the equation.
-12 + 12 + 44x = -1 + 12

Combine like terms: -12 + 12 = 0
0 + 44x = -1 + 12
44x = -1 + 12

Combine like terms: -1 + 12 = 11
44x = 11

Divide each side by '44'.
x = 0.25

Simplifying
x = 0.25

See similar equations:

| .35+3x=45+2x | | 4q+z=-9 | | -7x-4x=66 | | 3x-4=3x-5 | | 30v^3+25v^2-105v=0 | | -1/3y=11 | | 0,20=x*y-(x*y/100*5)-x | | -2(7w-4)+7w=3(w+4) | | 5/8x-5=16 | | 5/8x_5=16 | | 2x+x^2+3(4)+17= | | -4y+5+2y=7 | | -14.5+x=18.7 | | 2(2y)-5y=-4 | | -4+5+2y=7 | | -4+5+2y=y | | 2k+9=1 | | 18+9y= | | 8[5-(-6x-1)]=384x+104 | | 100=10(100) | | -3=-3y | | s^2+10s+9=0 | | 2+7(-2m-1)=-117 | | 10x+8=37 | | 8x-36=-2x-82 | | 40x+20=200 | | x/5+3=1 | | 30=7y-35+6 | | -5(u-6)=9u+2 | | 24+x+5x+90=360 | | 1.8z-0.8z+7.4=-6.6-4.1 | | (x-4)(x-5)=10 |

Equations solver categories